The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.2217/pgs.15.47
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 Gene Polymorphisms as Risk Factors for Atorvastatin Adverse Reactions: A Case–Control Study

Abstract: Our study demonstrated an association between atorvastatin-induced ADRs and genetic variants in the ABCG2 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 59 publications
(78 reference statements)
1
14
0
Order By: Relevance
“…Single nucleotide polymorphism of ABCG2 421C>A (p.Q141K) results in its reduced activity – mRNA expression is maintained, but protein expression and function is reduced by 50–70% due to enhanced susceptibility to proteasomal degradation . Variant allele carriage is associated with a higher systemic exposure to several statins and sulfasalazine and with an increased incidence of adverse effects of statins and gefitinib . The present data suggest that it enhances the effect of valproate on exposure to lamotrigine.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphism of ABCG2 421C>A (p.Q141K) results in its reduced activity – mRNA expression is maintained, but protein expression and function is reduced by 50–70% due to enhanced susceptibility to proteasomal degradation . Variant allele carriage is associated with a higher systemic exposure to several statins and sulfasalazine and with an increased incidence of adverse effects of statins and gefitinib . The present data suggest that it enhances the effect of valproate on exposure to lamotrigine.…”
Section: Discussionmentioning
confidence: 99%
“…The 421AA genotype has been associated with a 2.4-fold increased exposure to RVT,~2-fold increased exposures to ATV, FVT, and SVT, but no increased exposures to PIT or PVT [108]. Interestingly, carrying rs2231142 421A has been associated with an increased risk of myotoxicity with ATV [120], and in renal transplant recipients receiving FVT [105]. Both of these studies were small case control candidate gene studies and have not been confirmed in GWAS, although SRM GWAS analyses have included relatively few FVT cases to date [86,110,111,115].…”
Section: Abcb1 and Abcg2 Efflux Transportersmentioning
confidence: 99%
“…The mutated ABCG2 rs2231142 SNP has been previously associated with alterations in the pharmacokinetics of statins, with higher AUC being reported for atorvastatin and fluvastatin concentrations in 421A homozygotes vs 421C homozygotes . A case‐control study also showed that patients with the ABCG2 421CA or AA genotypes were 2.9 times more likely to develop adverse drug reactions—depending on the atorvastatin dose—than the ABCG2 421C homozygotes . Unfortunately, only one of our subjects carried this genotype.…”
Section: Resultsmentioning
confidence: 68%